Infragravity wave height dependency on short wave parameters – observations on the east coast of South Korea - Oh, Jung-Eun; Chang, Yeon S.; Ryu, Kyong Ho; Jeong, Weon Mu (Frontiers in Marine Science, 2023)
Infragravity waves (IGWs) that have lower wave frequencies than short waves (SWs) can cause significant impacts on coastal processes, such as beach erosion, when their amplitude increases toward the shore, specifically under energetic wave conditions. Therefore, it is important to precisely predict IGW shoaling based on SW conditions for scientific and engineering purposes. In this study, shoaling of IGWs was observed at three different sites along the east coast of South Korea based on continuous wave observations at various water depths. The nearshore IGW shoaling was dominant over the SWs, which was likely due to the energy transfer between the SWs and IGWs. Two types of SW parameters were employed to examine their correlations with IGWs, and linear dependences were observed for both types. However, the determination coefficient showed the opposite pattern between the two types, as it increased with decreasing depth with the wave energy flux. The comparison showed that the energy flux could be a preferred parameter type to represent the correlations of the IGW height in these calculations, as one formula could be developed for the depth-dependent proportional coefficients of the linear correlations when the energy flux was used. However, a discrepancy was also observed in the magnitude of the proportional coefficients, indicating that the IGW height over the SW parameters was higher in the sandy beaches than in the rocky seabed. Therefore, it could be assumed that seabed conditions may be an important factor for the process of IGW shoaling, but further evidence is needed.